2013
DOI: 10.1093/jat/bkt067
|View full text |Cite
|
Sign up to set email alerts
|

Detection of Synthetic Cannabinoids in Oral Fluid Using ELISA and LC-MS-MS

Abstract: Synthetic cannabinoids are often referred to as 'Spice' or K2 compounds. Detection of these compounds in oral fluid has, to date, been limited to chromatographic procedures such as liquid chromatography with tandem mass spectrometry detection. We report the first analytical immunoassay for the screening of some synthetic cannabinoids in oral fluid specimens collected with the Quantisal™ device. JWH-200 was chosen as the calibration standard, because parent compounds, not metabolites, are predominantly detected… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

3
33
0

Year Published

2013
2013
2017
2017

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 49 publications
(36 citation statements)
references
References 16 publications
3
33
0
Order By: Relevance
“…Cutoff optimization improved performance to 87.6% sensitivity, 85.2% specificity, and 85.4% efficiency. Conclusion: This highthroughput urine SC assay has good sensitivity and improved specificity and efficiency at modified cutoff concentrations.Bioanalysis (2014) 6(21) future science group Research Article Castaneto, Desrosiers, Ellefsen et al currently no regulated SC screening and confirmatory cutoffs, but SC markers were documented in hair [16], ante- [17,18] and postmortem blood [19], oral fluid [20][21][22], and urine [23][24][25][26][27] primarily by LC-MS/MS. Commercially available immunoassays also can provide rapid screening identification and semi-quantitative results for SC and metabolites, but critical assay evaluations are limited [22,28].…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…Cutoff optimization improved performance to 87.6% sensitivity, 85.2% specificity, and 85.4% efficiency. Conclusion: This highthroughput urine SC assay has good sensitivity and improved specificity and efficiency at modified cutoff concentrations.Bioanalysis (2014) 6(21) future science group Research Article Castaneto, Desrosiers, Ellefsen et al currently no regulated SC screening and confirmatory cutoffs, but SC markers were documented in hair [16], ante- [17,18] and postmortem blood [19], oral fluid [20][21][22], and urine [23][24][25][26][27] primarily by LC-MS/MS. Commercially available immunoassays also can provide rapid screening identification and semi-quantitative results for SC and metabolites, but critical assay evaluations are limited [22,28].…”
mentioning
confidence: 99%
“…Commercially available immunoassays also can provide rapid screening identification and semi-quantitative results for SC and metabolites, but critical assay evaluations are limited [22,28].…”
mentioning
confidence: 99%
“…Intercept [85] and Quantisal TM [97,101,124]. Kneisel et al [84] They also observed some degradation for JWH-073 and JWH-018 when stored at room temperature for one week, while when refrigerated, samples were stable.…”
Section: Oral Fluidmentioning
confidence: 99%
“…Moreover, cross-reactivity and false positives can occur, and as such, toxicologists recommend that all positive immunoassay findings must be retested and confirmed by chromatographic analysis. Immunoassay tests have been used for the screening of SCs in oral fluid [101] and their metabolites in urine samples [82,93,[102][103][104]. …”
Section: Immunoassay Techniquementioning
confidence: 99%
See 1 more Smart Citation